MODEL PENYELESAIAN SENGKETA PEMBIAYAAN BERMASALAH PADA BANK WAKAF MIKRO BERBASIS PESANTREN - Nurjamil, Siti Nurhayati, Ahmad Agung, Ine Risnaningsih (Fakultas Hukum Universitas Komputer Indonesia, 2019)
Design/methodology/approach-This research is an analytical descriptive research with normative juridical approach. The data were obtained from library research and field research through in-depth interviews with related parties including the management of the Micro Waqf Bank Islamic Microfinance Institution Ranah Indah Darussalam Ciamis West Java Indonesia and Commissioner of the Financial Services Authority of Indonesia then analyzed qualitatively. This research was conducted in Ciamis and Bandung West Java Indonesia. Finding- The finding of this study has confirmed that Sharia economic disputes are the absolute competencies of the Religious Courts based on Article 49 of Law Number 3 of 2006 concerning Amendments to Law Number 7 of 1989 concerning Religious Courts including disputes on BWM financing. In disputes that occur in troubled financing BWM the stages of completion are by intensive collection (cash collateral), rescheduling, reconditioning, or restructuring or also known as the stages of fulfillment of performance and deliberation and mediation between BWM management and customers involving other customers both in the scope â€œumpiâ€ and cluster to be dealt joint responsibility among customers so that the settlement of disputes through litigation in religious courts does not need to be taken by the parties. Keywords: Problematic Financing, Micro Waqf Bank, Dispute Resolution, Deliberation, non litigation